PENGARUH PENGENDALIAN PERSEDIAAN BAHAN BAKU TERHADAP PROSES PRODUKSI PRODUK MOUNTEA PADA PT TRITEGUH MANUNGGAL SEJATI - Ramli, Muh (Jurnal Ekonomi Balance, 2014)
MUH. RAMLI, 2018. The Influence of Controlling the Supply of Raw Materials on the Production Process of Mountea Products at PT Triteguh Manunggal Sejati. This study aims to determine the effect ofControlling Raw Material inventrory on the Production Process of Mountea Products at PT Triteguh Manunggal Sejati.  The type of this research used in this research is quantitative research with approach eksplanatori.sampel in this research as much 60 responder. This research uses simple linear regression analysis technique with SPSS program and using data from respondent and documentation from PT Triteguh Manunggal Sejati. The result of the simple linear regression test is Y = Y= 8,461+ 768, which means that the constant value of 8,461 with regression coefficient 768 which states the direction of influence of X variable to Y is positive and sig0,004<0,05 which means that work stress significantly employee performance on PT Triteguh Manunggal Sejati. As for the influence of the raw material inventory control variables on the production process is 60% while the remaining 40% is influenced by other objects.